Imaging features from pretreatment CT scans are associated with clinical outcomes in nonsmall‐cell lung cancer patients treated with stereotactic body radiotherapy. Issue 8 (24th June 2017) - Li, Qian; Kim, Jongphil; Balagurunathan, Yoganand; Liu, Ying; Latifi, Kujtim; Stringfield, Olya; Garcia, Alberto; Moros, Eduardo G.; Dilling, Thomas J.; Schabath, Matthew B.; Ye, Zhaoxiang; Gillies, Robert J.
Abstract : Purpose: To investigate whether imaging features from pretreatment planning CT scans are associated with overall survival (OS), recurrence‐free survival (RFS), and loco‐regional recurrence‐free survival (LR‐RFS) after stereotactic body radiotherapy (SBRT) among nonsmall‐cell lung cancer (NSCLC) patients. Patients and methods: A total of 92 patients (median age: 73 yr) with stage I or IIA NSCLC were qualified for this study. A total dose of 50 Gy in five fractions was the standard treatment. Besides clinical characteristics, 24 "semantic" image features were manually scored based on a point scale (up to 5) and 219 computer‐derived "radiomic" features were extracted based on whole tumor segmentation. Statistical analysis was performed using Cox proportional hazards model and Harrell's C‐index, and the robustness of final prognostic model was assessed using tenfold cross validation by dichotomizing patients according to the survival or recurrence status at 24 months. Results: Two‐year OS, RFS and LR‐RFS were 69.95%, 41.3%, and 51.85%, respectively. There was an improvement of Harrell's C‐index when adding imaging features to a clinical model. The model for OS contained the Eastern Cooperative Oncology Group (ECOG) performance status [Hazard Ratio (HR) = 2.78, 95% Confidence Interval (CI): 1.37–5.65], pleural retraction (HR = 0.27, 95% CI: 0.08–0.92), F2 (short axis × longest diameter, HR = 1.72, 95% CI: 1.21–2.44) and F186 (Hist‐Energy‐L1, HR = 1.27, 95% CI: 1.00–1.61); The prognostic model for RFS contained vessel attachment (HR = 2.13, 95% CI: 1.24–3.64) and F2 (HR = 1.69, 95% CI: 1.33–2.15); and the model for LR‐RFS contained the ECOG performance status (HR = 2.01, 95% CI: 1.12–3.60) and F2 (HR = 1.67, 95% CI: 1.29–2.18). Conclusions: Imaging features derived from planning CT demonstrate prognostic value for recurrence following SBRT treatment, and might be helpful in patient stratification.